GAMES IN WRITING SKILL OF EFL LEARNERS: DO THEY GIVE ANY IMPACT? - zaitun zaitun; Muhamad Sofian hadi; Dian Rosydiyanti (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This research aimed to find out whether or not games affected the ability of EFL learners’ descriptive text writing skill. The research was conducted at SMP AN-NURMANIYAH, Tangerang. There were 39 students of 7th grade participated in this study as the sample chosen through cluster random sampling. The study applied quantitative method with pre-experimental research design and used both pre-test and post-test as the instruments in collecting the data. The data was analyzed statistically by using t-test. The result of this study showed; mean of students’ pre-test was 54.8 while mean score of their post-test was 82.5. The statistical calculation revealed that the result of t-calculation (tcal) t-table (tt), in which tcal obtained was 7.414 while tt was 2.042 with the significant level of 5% (0.05). Thus, the alternative hypothesis (H1) was accepted while the null hypothesis (H0) was rejected. Referring to these results, this research study concluded that games gave significant effect to the skill of 7th graders’ descriptive text writing.